PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DALAM MENGGUNAKAN JASA BUILDING AUTOMATIC SYSTEM PT. AZBIL BERCA INDONESIA - Tiarah; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
The research objective was to determine the effect of product quality and service quality on customer satisfaction in using Building Automatic System services at PT. Azbil Berca Indonesia. The analytical method was used, is quantitative analysis, with using test instruments, coefficient of determination, and multiple linear regression analysis. Simultaneously test of product quality variables and service quality on customer satisfaction in using Building Automatic System services at PT. Azbil Berca Indonesia, was indicated by F count is bigger than F table or with sig. prob is smaller than 0.05. Considering these results, the hypothesis Ho is rejected, Ha is accepted, which mean there is a simultaneously effect of product quality and service quality on customer satisfaction in using Building Automatic System services at PT. Azbil Berca Indonesia